Magnetic Resonance Imaging of Arthritis of the Knee - Rowbotham, Emma L.; Grainger, Andrew J. (Seminars in Musculoskeletal Radiology, 2017)
The knee joint is involved in a wide variety of arthritides, and imaging has always played a major role in both aiding diagnosis and assessing the severity of such diseases. Plain film radiography has traditionally been used as the primary imaging modality for radiographic diagnosis of arthritis. However, magnetic resonance imaging (MRI) shows a greater sensitivity to both the bone and soft tissue features of this group of conditions. This article reviews the imaging features of osteoarthritis (OA) of the knee shown on MRI and the criteria used to diagnose this condition. It also discusses imaging features that suggest the underlying arthropathy is not OA.
Keywords: MRI; magnetic resonance imaging; arthritis; osteoarthritis; knee